2005
DOI: 10.1016/j.cell.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Multiple Sulfatase Deficiency and Mechanism for Formylglycine Generation of the Human Formylglycine-Generating Enzyme

Abstract: Sulfatases are enzymes essential for degradation and remodeling of sulfate esters. Formylglycine (FGly), the key catalytic residue in the active site, is unique to sulfatases. In higher eukaryotes, FGly is generated from a cysteine precursor by the FGly-generating enzyme (FGE). Inactivity of FGE results in multiple sulfatase deficiency (MSD), a fatal autosomal recessive syndrome. Based on the crystal structure, we report that FGE is a single-domain monomer with a surprising paucity of secondary structure and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
241
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(260 citation statements)
references
References 51 publications
9
241
0
10
Order By: Relevance
“…So far, 30 mutations in SUMF1 have been described in MSD patients including nine nonsense and 21 missense mutations [Dierks et al, 2003;Cosma et al, 2003;Cosma et al, 2004;Dierks et al, 2005;Diaz-Font et al, 2005]. Mature FGE is made up of a 341-amino acid polypeptide, which adopts a single domain monomeric structure with a unique fold .…”
Section: Introductionmentioning
confidence: 99%
“…So far, 30 mutations in SUMF1 have been described in MSD patients including nine nonsense and 21 missense mutations [Dierks et al, 2003;Cosma et al, 2003;Cosma et al, 2004;Dierks et al, 2005;Diaz-Font et al, 2005]. Mature FGE is made up of a 341-amino acid polypeptide, which adopts a single domain monomeric structure with a unique fold .…”
Section: Introductionmentioning
confidence: 99%
“…13,20,29,21 ECL signals were quantified using the AIDA software package (Raytest, Straubenhardt, Germany). Endogenous FGE in MSD fibroblasts was detected using ECL femto substrate and enhancer diluted 1:10 in ECL solution (Pierce, Bonn, Germany).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…25 Until now, more than 30 different SUMF1 mutations were found, most of which are missense mutations. 9,23,26,20,27 In a first approach, we investigated the consequences of four different MSD causing SUMF1 mutations on FGE 13 expression, localization, stability and activity in either an overexpressing cell-culture model or in patient fibroblasts. We found that all four variant FGE proteins could be expressed in HT-1080 cells, correctly localizing to the ER.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGE oxidizes the genetically-encoded cysteine residue to the aldehyde-bearing residue formylglycine (fGly) during protein expression in either E. coli or mammalian cells (Scheme 1 A). [35] The aldehyde can then be modified by hydrazone or oxime formation (Scheme 1 B). [36] Thus, the aldehyde tag serves as a means for site-specific introduction of azides or cyclooctynes onto recombinant proteins through small-molScheme 1.…”
mentioning
confidence: 99%